Analisis Faktor Penyebab Lamanya Waktu Penyediaan Rekam Medis Rawat Jalan di Rumah Sakit Baladhika Husada Jember - Deanissa Aulia; Gamasiano Alfiansyah; Maya Weka Santi; Sabran (Manajemen Pelayanan Kesehatan, 2024)
The average waiting time to obtain outpatient medical records at the Baladhika Husada Jember Hospital reached 56.7 minutes, exceeding the minimum service standard which should be no more than 10 minutes. The aim of the research was to analyze the factors that cause the long time to provide outpatient medical records at the Baladhika Husada Jember Hospital used the 5M management elements. This research used qualitative methods with data collection techniques of documentation, observation, interviews, urgency, seriousness, and growth. The research subjects were 1 head of the medical records unit, 5 filling officers, 4 registration officers, and 3 nurses. The research results were show that the man variable was the lack of knowledge of officers. Method, there was no SOP for providing outpatient medical records. Machine, SIMRS error. Media, filling rooms were not strategic and there were officers who arrived late. Motivation without punishment. Efforts to fix the problem include moving the filling room on the 2nd floor adjacent to the outpatient registration area on the 1st floor and switching to using Electronic Medical Records. The advice given to Baladhika Husada Hospital is to relocate the filling room and develop the existing SIMRS to become 100% Electronic Medical Records.